2014
DOI: 10.1016/j.neuroimage.2014.06.067
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurement of glutamate loss is associated with synapse loss in a mouse model of tauopathy

Abstract: Glutamate is the primary excitatory neurotransmitter in the brain, and is implicated in neurodegenerative diseases such as Alzheimer’s disease (AD) and several other tauopathies. The current method for measuring glutamate in vivo is using proton magnetic resonance spectroscopy (1H MRS), although it has poor spatial resolution and weak sensitivity to glutamate changes. In this study, we sought to measure the effect of tau pathology on glutamate levels throughout the brain of a mouse model of tauopathy using a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 30 publications
8
58
0
Order By: Relevance
“…Increased glutamate levels in the dorsal hippocampus persisted through late stage pathology so that GluCEST levels in PS19 mice exceeded those in WT mice by 13 months, agreeing with our previous report (Crescenzi et al, ). Increased glutamate levels observed in the PS19 hippocampus may be consistent with evidence of neuroprotective physiology, specifically hyperperfusion and hypermetabolism.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increased glutamate levels in the dorsal hippocampus persisted through late stage pathology so that GluCEST levels in PS19 mice exceeded those in WT mice by 13 months, agreeing with our previous report (Crescenzi et al, ). Increased glutamate levels observed in the PS19 hippocampus may be consistent with evidence of neuroprotective physiology, specifically hyperperfusion and hypermetabolism.…”
Section: Discussionsupporting
confidence: 92%
“…Contributions from other labile amine and amide protons contribute to <30% of the GluCEST asymmetry. Detailed descriptions of the GluCEST technique can be found in Cai et al (), Haris et al (), and Crescenzi et al ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 8 and 12–14 months of age, interestingly, there were reduced glutamate, but increased putrescine, levels in PS19 mice for all six regions (except for glutamate in the thalamus), indicating an age-related shift of channelling L-ornithine to produce putrescine. Crescenzi et al (2014) reported reduced glutamate levels in the CA (29%), but not the dentate gyrus, sub-regions of the hippocampus in 20-month PS19 mice using proton magnetic resonance spectroscopy. The present study found a 30% reduction in glutamate in the whole hippocampus of 12–14-month PS19 mice, which appears to be consistent with this earlier report.…”
Section: Discussionmentioning
confidence: 97%
“…GluCEST imaging offers a resolution of 0.27 mm × 0.27 mm × 2 mm for animal model and 1.9 mm × 1.9 mm × 2 mm for human subjects with an imaging time of around 16s per slice (1 average), which is much better compared to conventional chemical shift imaging techniques in terms of spatial and temporal resolution. The total scan time is around 12 mins, including the acquisition of B0 and B1 maps needed for corrections (92, 93). …”
Section: Chemical Exchange Saturation Transfer (Cest) Imaging In Bmentioning
confidence: 99%